Of light and shadows: Buddhism, cinema, and the question of diffused religion in modern China - NG, Teng-kuan (Institutional Knowledge at Singapore Management University, 2024)
While the scholarship on premodern Chinese Buddhism has explored the tradition’s rich diffusion throughout various realms of sociocultural life, the study of modern Chinese Buddhism leans heavily towards its monastic, institutional, and overtly “religious” forms. This split mirrors the logic of modern secularization, whereby religion should be rationally differentiated from the broader social fabric, institutionalized, and delimited within its own discrete functional sphere. This article rethinks the putative rupture between Chinese Buddhism’s past and present incarnations. Through the prism of cinema, a technology that arrived on Chinese shores at the same moment as the Western concept of religion, I illuminate the overlooked continuities between premodern and modern diffusions of Buddhist thought and culture. Drawing from film theory, evolutionary anthropology, and religion and media studies, the first section constructs a selective genealogy of proto-cinematic phenomena across the history of religions in China. I highlight three transmedia genres—lantern shadow plays, medieval “transformation tableaux” paintings, and late imperial vernacular novels—that illustrate how Buddhistic “sight and sound” was enmeshed with religious pedagogy, ritual practices, social ethics, and popular entertainment in premodern society. The second section examines the ways in which film’s advent, indigenization, and growth overlapped with coeval transformations of the Chinese religious field during the late nineteenth and early twentieth centuries. At a time when traditional religiosities were being institutionalized or anathemized by political power, the cinema, I argue, served as an intermedial space where Buddhist morals, myths, aesthetics, and epistemic sensibilities continued unobstructed, at least until the early 1930s. Finally, I conclude with brief reflections on some avenues for future research in Chinese Buddhism, secular Buddhism, and religion and media studies.